Grammatical Permissibility In What Is Not Mentioned In The Syntax Of The Quranic Readings - Reda Rafi, Reda Rafi (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : The research paper deals with an important issue in the Quranic grammar, which is the permissible grammatical referencing in the Quran which is not mentioned in the Quranic Readings. This referencing serves and enriches the Arabic grammar. It also proves the competency of Arab grammarians in their domain and their ability to interpret speech according to the Arabic norms and methods, even if it is not found in the Quran Readings. Therefore, this research seeks to study models of what is permissible in Arabic and did not come with the Reading, which are models that show the role of scholars in the service of Arabic grammar based on the Quranic Readings and their parsing.